2014
DOI: 10.4067/s0718-58392014000400014
|View full text |Cite
|
Sign up to set email alerts
|

Salt-induced root protein profile changes in seedlings of maize inbred lines with differing salt tolerances

Abstract: Salt stress is one of the severest growth limited-factors to agriculture production. To gain in-depth knowledge of salt-stress response mechanisms, the proteomics analysis from two maize (Zea mays L.) inbred lines was carried out using twodimensional gel electrophoresis (2-DGE) and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF/TOF-MS). There were 57 salt-regulated proteins identified, 21 and 36 proteins were differentially regulated in inbred lines 'Nongda 1145' (salt-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Our data are consistent with those of Cheng et al [41], who described an enhanced abundance of proteins involved in ATP synthesis, protein refolding, carbohydrate metabolism, and transcription in salt-tolerant plants. Additionally, Athar et al [19] reported upregulation of proteins related to protein translation, protein proteolysis, and energy production.…”
Section: Cluster Of Orthologous Groups Analysissupporting
confidence: 93%
“…Our data are consistent with those of Cheng et al [41], who described an enhanced abundance of proteins involved in ATP synthesis, protein refolding, carbohydrate metabolism, and transcription in salt-tolerant plants. Additionally, Athar et al [19] reported upregulation of proteins related to protein translation, protein proteolysis, and energy production.…”
Section: Cluster Of Orthologous Groups Analysissupporting
confidence: 93%
“…Researchers have been active in addressing these questions. A root proteomics study of maize seedlings exposed to 150 mM NaCl stress showed that the responses were quanti- and qualitatively different between a sensitive and a tolerant inbred line ( Cheng et al, 2014 ). The authors suggested that an enhanced antioxidative defense system, allied to other processes, are the fighting arms of tolerant lines.…”
Section: Introductionmentioning
confidence: 99%
“…For example, two inbred maize lines had 57 differentially expressed proteins under salt stress, related to energy metabolism, carbohydrate metabolism, antioxidant system, secondary metabolite biosynthesis, protein refolding, protein translation, and transcriptional regulation. This specific network of metabolic pathways can be used as salt stress imprints (Cheng et al, 2014). Such changes in metabolism are due to salt stress sensor proteins and metabolic biosynthesis enzymes directly involved in the acquisition of salinity tolerance (Hey et al, 2009;Barajas-Lopez et al, 2018;Yang et al, 2019;Jha et al, 2022).…”
Section: Salt Stress Proteins Involved In Different Metabolismsmentioning
confidence: 99%
“…While working with halophytes (Suaeda maritima, Salicornia brachiata) Benjamin et al (2020) found up-regulation of eIF4A in S. brachiata under 200 mM NaCl salinity stress conditions, which indicated its involvement in salt tolerance of halophyte. Substantial increase in abundance of eIFs, EFs and ribosomal proteins in salt tolerant cultivar as compared to that in salt sensitive cultivar of rice (Frukh et al, 2020) and maize (Cheng et al, 2014). Protein translation effector (EF1B) regulates translation fidelity was up-regulated under salt stress in salt tolerant tomato accession than that in salt sensitive accession (Nveawiah-Yoho et al, 2013).…”
Section: Salt Stress Proteins Involved In Posttranscriptional and Pos...mentioning
confidence: 99%